“Teman Terang Creative Project” – Visual Communication Design Aspect in a Creative Charity Movement for Children in No Electricity Remote Area - Riskhi Bestari (Institut Seni Indonesia Yogyakarta, 2014)
“Teman Terang Creative Project” is a creative charity project which held by students/visualartistsaround Visual Communication Design environment under the authority of StudioDiskom (Program Organization) and lead by Riskhi Bestari. This charity project involvingstudents/visual-artists to dedicates their artworks to the children (elementary school gradestudent) in no electricity remote area as an act of care and attention. By choosing Semprong,The-traditional-lantern-kind-of-lamp as the design object, with some innovation and designideas, but still keeping its unique traditional look; we try to use this Semprong Lamp as a mediafor applying our arts, to deliver our ideas, shows up our expression and as a symbol of spirit andmotivation, care and attention to the children in remote & no electricity for their education.